DUKUNGAN SOSIAL DAN SPIRITUAL DALAM MEMBENTUK RESILIENSI REMAJA PADA MASA PANDEMI COVID-19 DI KELURAHAN KEMAYORAN BANGKALAN - Widya Lita Fitrianur; Ervi Suminar; Sri Yuliastutik (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2022)
Changes in the learning process due to the Covid-19 pandemic have become a source of stress for adolescents. The change from face-to-face methods to online learning must be able to be adapted well by teenagers. One of the important components in the adaptation process is resilience. This study aims to determine the relationship between social and spiritual support and adolescent resilience during the COVID-19 pandemic. The research design was used cross sectional with a sample of 142 adolescents. Data retrieval was using google forms to minimize contact with respondents. The result showed a relationship between social support p = 0.001 and spirituality p = 0.000 with adolescent resilience during the covid-19 pandemic. Adolescents with high social support have a 9x chances of forming high resilience and adolescents with a high spiritual level have a 0.17x chances of forming high resilience. Adolescents need to get a good social support from family, friends and the environment, and develop a high spiritual level to form resilience and prevent the emergence of psychosocial disorders. Keywords: Social Support, Spiritual, Resilience, Adolescent